1968
DOI: 10.1037/h0025416
|View full text |Cite
|
Sign up to set email alerts
|

Aversion to sucrose produced by contingent x-irradiation: Temporal and dosage parameters.

Abstract: Rats were familiarized with milk for 5 days. A few days later, experimental Ss drank sucrose solution and after 3.5-32 hr. were exposed to 50 r. of X-rays. Sham controls were not X-irradiated. Irradiated controls ate chow prior to irradiation. In a subsequent preference test, those experimental Ss irradiated 6.5 hr. or less after sucrose consumption exhibited an aversion to sucrose relative to both type of controls. In a similar experiment, rats exposed to 50, 150, or 250 r. 7 hr. after consuming sucrose solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(107 citation statements)
references
References 11 publications
7
100
0
Order By: Relevance
“…These taste aversions can be learned despite long delays between the CS (taste) and the US (poisoning), even when only a single trial is employed (Smith & Roll, 1967). Other parametric studies have demonstrated that the magnitude of the aversion varies directly with the concentration of the CS (Dragoin, 1971), and of the US (Revusky, 1968).…”
Section: Resultsmentioning
confidence: 98%
“…These taste aversions can be learned despite long delays between the CS (taste) and the US (poisoning), even when only a single trial is employed (Smith & Roll, 1967). Other parametric studies have demonstrated that the magnitude of the aversion varies directly with the concentration of the CS (Dragoin, 1971), and of the US (Revusky, 1968).…”
Section: Resultsmentioning
confidence: 98%
“…Yet although 8-12 h does appear to be the point beyond which animals do not learn taste aversions (see, however, Etscorn & Stephens, 1973), within this limit the delay interval is subject to a number of manipulations. For example, increases in the concentration of the taste stimulus (Andrews & Braveman, 1975;Braun & Rosenthal, 1976) or in the dose of the toxin (Revusky, 1968) increase the delay over which animals can learn the aversion. Similar effects have been reported with variations in the duration of the taste exposure (Deutsch, 1978) .…”
Section: Long-delay Taste Aversion Learning: Effects Of Repeated Triamentioning
confidence: 99%
“…In the taste aversion procedure, an animal is presented with a novel taste and subsequently made ill. On later exposure to the taste, the animal typically avoids its consumption (see Garcia, Ervin, & Koelling, 1966) . Robust taste aversions have been conditioned with extended delays between taste presentation and toxicosis (e.g., 9-12 h, see Nachman, 1970;Revusky , 1968;Smith & Roll, 1967; see Etscorn & Stephens, 1973, for a report of conditioned aversion with a delay of 24 h between between taste exposure and subsequent toxicosis). In a review of taste aversion learning, Klosterhalfen and Klosterhalfen (1985) advanced the position that the ability of animals to form associations over long delays within the CT A procedure is a function of the specific conditioned stimulus used in taste aversion research, that is, taste .…”
mentioning
confidence: 99%